Land politics under Kenya's new constitution: Counties, devolution, and the National Land Commission - Catherine Boone; Alex Dyzenhaus; Seth Ouma; James Kabugu Owino; Catherine W. Gateri; Achiba Gargule; Jackie Klopp; Ambreena Manji (London School of Economics and Political Science (LSE), Department of International Development, 2016)
Kenya's new constitution, inaugurated in August 2010, altered the institutional structure of the state in complex ways. The general motivation behind reform was to enhance the political representation of ordinary citizens in general and that of marginalized ethno-regional groups in particular, and to devolve control over resources to the county level. In the land domain, reform objectives were as explicit and hard-hitting as they were anywhere else. Reform of land law and land administration explicitly aimed at putting an end to the bad old days of overcentralization of power in the hands of an executive branch considered by many to be corrupt, manipulative, and self-serving.
Keywords: 330; Kenya; Devolution; Land laws; Reform; Governance; Rural livelihoods